miR-142-5p Disrupts Neuronal Morphogenesis Underlying Porcine Hemagglutinating Encephalomyelitis Virus Infection by Targeting Ulk1 - Li, Zi; Lan, Yungang; Zhao, Kui; Lv, Xiaoling; Ding, Ning; Lu, Huijun; Zhang, Jing; Yue, Huiqing; Shi, Junchao; Song, Deguang; Gao, Feng; He, Wenqi (Frontiers in Cellular and Infection Microbiology, 2017)
Porcine hemagglutinating encephalomyelitis virus (PHEV) invades the central nervous system (CNS) and causes neurodegenerative disease in suckling piglets, but the understanding of its neuropathogenicity for neurological dysfunction remains limited. Here, we report that miR-142-5p is localized to neurons and negatively regulates neuronal morphogenesis in porcine hemagglutinating encephalomyelitis (PHE). This phenotype was mediated by miR-142-5p inhibition of an mRNA encoding unc-51-like-kinase1 (Ulk1), which controls axon outgrowth and dendrite formation. Modulating miR-142-5p activity by microRNA mimics or inhibitors induced neurodegeneration, including stunted axon elongation, unstable dendritic spine formation, and irregular swelling and disconnection in neurites. Relieving Ulk1 mRNA repression in primary cortical neurons by miR-142-5p antagomirs or replication-deficient adenoviruses encoding Ulk1 (Ad5-Ulk1), which improved rescue of nerve injury, restricted viral replication, and increased survival rate in mice underlying PHEV infection. In contrast, disrupting Ulk1 in RNAi-expressing neurons mostly led to significantly shortened axon elongation and/or an abnormally large number of branched dendrites. Taken together, we demonstrated that the abnormal neuronal morphogenesis underlying PHEV infection was mainly caused by functional mRNA repression of the miR-142-5p target Ulk1. Our data revealed that PHEV adapted to use spatiotemporal control of host microRNAs to invade CNS, and provided new insights into the virus-associated neurological dysfunction microenvironment.